Excess molar volumes and excess viscosities of the 2,2,4-trimethylpentane (1) + 3-methyl-1-butanol (2) and propan-2-ol (3) ternary system at 298.15 K - Salas, J.A. (2006)
This paper reports experimental densities and viscosities of the ternary system 2-2-4-trimethylpentane + 3-methyl-1-butanol + propan-2-ol and the binary systems 2-2-4-trimethylpentane (isooctane) + 3-methyl-1-butanol (isoamyl alcohol), 2-2-4-trimethylpentane (isooctane) + propan-2-ol (isopropyl alcohol), and 3-methyl-1-butanol + propan-2-ol, over the entire range of composition at 298.15 K. Excess molar volume, excess viscosity and the excess energy of activation for viscous flow were evaluated from the experimental data obtained. These derived properties for binary and ternary systems were fitted to Redlich-Kister's and Cibulka's equations, respectively. Flory's statistical theory has been applied to predict excess molar volumes for ternary system. For viscosities we applied Grunberg and Nissan, Katti and Chaudhri, Bloomfield and Dewan and Wu equations and finally the GC-UNIMOD model. © 2005 Elsevier B.V. All rights reserved.